This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(4x + 5x)(4x - 5y) - (3x + 2y)(3x - 2y)
first , see the first term ( i mean 4x)
multiply it with (4x - 5y)
u will get,
16x² - 20xy
like wise multiply +5x with (4x - 5y)
u will get,
20 x²- 25 xy
now (4x + 5x)(4x-5y) = 16x²-20xy+20x²-25xy
now,u have
-(3x +2y)(3x-2y)
similarly how u did above ,
multiply -3x with ( 3x-2y)
u will get,
u should take -2y and mul with (3x-2y)
u will get,
-6xy + 4y²
now-(3x+2y)(3x-2y) = -9x²+6xy-6xy+4y²
now, totally,

(4x+5x) (4x-5y)-(3x2y)(3x-2y)=16x²-20xy+20x²-25xy-9x²+6xy-6xy+4y²
 arrange in an easy way to solve,
                                             = 16x²+20x²-9x²+4y²-20xy-25xy+6xy-6xy
                                             = 37x²+4y²-45xy
here, +6xy and - 6xy gets cancelled
u need to concentrate on symbols :
(i) plus×plus = plus
(ii)plus ×minus = minus
(iii) minus × minus = plus
(iv) minus ×plus = minus

still any doubts?
no thankuuuuuuuuuu so much
brainliest please
yes i sure after sometimes i will mark u as the brainleast